Ultrasound Guided Femoral Cannulation and Percutaneous Perfusion of the Distal Limb for VA ECMO. Issue 3 (10th March 2014) - Benassi, Filippo; Vezzani, Antonella; Vignali, Luigi; Gherli, Tiziano
Abstract Percutaneous cannulation allows a prompt approach for establishing veno‐arterial extracorporeal membrane oxygenation in acute cardiopulmonary failure. Access to an artery or a vein can sometimes be difficult with severe complications also with percutaneous approach. To reduce morbidity, we describe our technique of a real‐time ultrasound cannulation of the femoral vessels. doi: 10.1111/jocs.12319 (J Card Surg 2014;29:427–429)